Investigation of electrical properties of organophosphazene layer based photodiode - Koran, Kenan; Arif, Bilal; Ali, Dilawar; Dere, Aysegul; Ozen, Furkan; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Elsevier, 2020)
New cyclotriphosphazene compound bearing dioxyphenylcoumarin group (DCP-1) was synthesized from the reactions of 7,8-dihydroxy-3-(4-chlorophenyl)coumarin (3) containing chlorine as a side group at para position with cyclotriphosphazene (DCP). The structures of the compounds were determined using H-1, C-13 APT, P-31 NMR, FT-IR and elemental analysis spectroscopy methods. The organic layer was deposited onto the p-Si substrate to obtain an Al/p-si/phosphazene (DCP-1)/Al diode. The photoresponse and photocapacitance properties of the diode were analyzed under various solar light intensities. The photocurrent and photocapacitance results suggest that the studied device exhibits both photodiode and photocapacitor behavior. The diode indicates a linear photoresponse behavior. The photoswitching behavior of the diode is controlled by solar light intensity. The interface states density of the diode was found to be order of 10(12) eV(-1)cm(2). The value of interface states density indicates that the photocapacitor behavior of the diode is significant for photocapacitor applications.
Keywords: Bandgap; Electrical properties; Cyclotriphosphazene; Coumarin-phosphazene